Proximate Composition, Energy and Nutritional Value of Local Malt (Asaana) Prepared from Maize in Ghana - Benjamin, Bartels; Ama, Atakora Priscilla; Yao, Gadzekpo Victor Patrick (International Journal of Environment, Agriculture and Biotechnology, 2023)
Background and objectives: “Asaana” is a local malt consumed by majority of Ghanaians of all ages in all the cultures due to its refreshing and nutritional benefits. Since traditional women and methods prepare it, no nutritional information is available during sale. In addition, research data about it is very scanty. This study therefore aims at determining its nutritional and potential energy value to enrich the existing data. Method: The study focused on two types of Asaana preparations. A sample from a local producer prepared by the traditional recipe; and another prepared in the laboratory from two varieties of maize (yellow and white) according to the traditional recipe. Proximate analysis and energy evaluation done to determine nutritional value and energy potential. Results: The white variety had higher moisture (94.20± 0.01%), P (6324.16 ±36.31µg/g), K (6162.76± 128.07 µg/g), Na (718.08± 4.51 µg/g), Zn (865.65± 9.09 µg/g) contents and fat energy (0.44kj/g). The yellow variety recorded higher dry matter (7.39 ± 0.00%), and carbohydrate (88.33± 0.20%) contents and carbohydrate energy (15.0 kj/g). The traditional preparation had higher protein (8.95± 0.11%), fat (1.40± 0.03%), fibre (4.04± 0.08%), Ca (11600 ±76.68 µg/g), Mg (2000.48± 28.20 µg/g), Fe(300.45 ±9.86 µg/g)contents and Protein energy(1.52kj/g). Conclusion: “Asaana” is potentially nutritious and provides basic energy needed for physiological activities.